On some classes of almost periodic functions in abstract spaces - Dariusz Bugajewski; Gaston M. N'Guérékata (International Journal of Mathematics and Mathematical Sciences)
We deal with C(n)-almost periodic functions taking values in a Banach space. We give several properties of such functions, in particular, we investigate their behavior in view of differentiation as well as integration. The superposition operator acting in the space of such functions is also under consideration. Some applications to ordinary as well as partial differential equations are presented. Moreover, we introduce the class of the so-called asymptotically C(n)-almost periodic functions and give some of their properties.